Comparison of Outcomes Between Anti-Nuss Operation and Modified Anti-Nuss Operation Using a Flexible Plate for Correcting Pectus Carinatum: A Retrospective Study - Wang, Lei; Liu, Juan; Shen, Saie; Li, Yao; Feng, Tienan; Li, Guoqing; Xiao, Haibo; Hu, Fengqing (Frontiers in Surgery, 2021)
Introduction: The anti-Nuss procedure has gradually been found to have several shortcomings in clinical practice. Accordingly, our department previously designed and introduced a new steel plate. However, there is limited evidence regarding its safety and efficacy. Thus, we aim to compare the efficacy and safety of the conventional anti-Nuss operation with those of a modified anti-Nuss operation using a flexible plate. Methods: Patients with pectus carinatum who underwent surgery between January 2014 and August 2019 were consecutively enrolled in this single-center, retrospective study. In all, 53 patients underwent the modified procedure using the new steel plate (new procedure group), whereas 43 underwent the conventional anti-Nuss procedure (traditional procedure group). Outcome analysis was performed using SPSS to compare the intraoperative and postoperative short-term outcomes. Results: All patients in the new procedure group had shorter operation duration (75.23 ± 11.90 vs. 82.45 ± 9.30 min, p = 0.008), postoperative hospitalizations (3.42 ± 0.95 vs. 4.64 ± 1.53 days, p = 0.039), and plate removal surgery durations (40.60 ± 3.47 vs. 60.30 ± 9.75 min, p = 0.041) than patients in the traditional procedure group. There were no significant differences in the length of incision, postoperative Haller index, cost, postoperative surgical outcome, and incidence of complications between the two groups. Conclusion: Our data reveal that the main clinical outcomes were similar for after anti-Nuss operation and modified anti-Nuss operation. However, the modified procedure for pectus carinatum had a shorter operation duration, postoperative hospitalization, and plate removal surgery duration.